The emerging role of the exosomal proteins in neuroblastoma - Bhavsar, Swapnil Parashram; Morini, Martina (Frontiers in Oncology, 2024)
Exosomes are a subclass of extracellular vesicles shown to promote the cancer growth and support metastatic progression. The proteomic analysis of neuroblastoma-derived exosomes has revealed proteins involved in cell migration, proliferation, metastasis, and in the modulation of tumor microenvironment -thus contributing to the tumor development and an aggressive metastatic phenotype. This review gives an overview of the current understanding of the exosomal proteins in neuroblastoma and of their potential as diagnostic/prognostic biomarker of disease and therapeutics.